Bird preservation, research & visitors centre - Moffat, S. L. (University of the Free State, 2016)
This design dissertation investigates the proposal of a Bird Preservation, Research and Visitors’ Centre on Malgas Island in Saldanha Bay. The aim of the project is to assist the South African National Parks Board within the West Coast National Park with the observation, research and preservation of the planet’s largest colony of Cape Gannets, whose habitat is the volatile surface of Malgas Island, and whose numbers are decreasing with each passing year. In doing so, the project also aims to draw attention to and memorialise these intriguing creatures that, for most, remain nameless and undiscovered. My interest in the topic of this dissertation stems from a personal fascination with the natural environment, more specifically, with the ocean. I am greatly interested in the fact that oceans are the direct providers and lifeblood to more than two thirds of our planet’s inhabitants, both human and otherwise. One species that is particularly dependent on the sea, and which is currently on the verge of extinction, is the Morus Capensis, the Cape Gannet. This study has been organised into four main parts. The first part explores the project’s challenges and aims. Here, various challenges were identified by means of an investigation into the typology, topology, morphology and tectonic potential of the design which, in turn, generated problem statements and aims. The second part provides a detailed discussion on the research design and methodology in terms of the various research methods that were used, indepth investigation, the grounding of various arguments in personal explorations, as well as numerous literature reviews and precedent studies that inform this project. The third part explores the design and tectonic synthesis. The design and construction processes were thoroughly explained and followed, resulting in a final design solution and product. The last part of the dissertation reflects on and evaluates the entire design process and its success or lack thereof.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2016
Keywords: Malgas Island, Saldanha Bay; Preservation; Ecological ethics; Agency; Cape Gannet; Vernacular; Unassuming architecture; Observation; Anthropocentric vs ecocentric; Sustainable architecture